Beta frequency binaural beats combined with preferred music enhance combat performance and recovery responses in amateur kickboxers: a randomized crossover trial - Jebabli, Nidhal; Boujabli, Manar; Khlifi, Mariem; Ouerghi, Nejmeddine; Bouassida, Anissa; Abderrahman, Abderraouf Ben; Dhahbi, Wissem; Tillaar, Roland van den (Frontiers in Psychology, 2025)
BackgroundWhile binaural beats and preferred music demonstrate established ergogenic effects independently, their synergistic potential during combat sports recovery remains unexplored. This study aimed to investigate the combined effect of 15 Hz beta-frequency binaural beats with preferred music during inter-round recovery enhances striking performance and psychophysiological responses in kickboxing athletes.MethodsNineteen amateur kickboxers (age: 21.5 ± 1.8 years; body mass: 68.7 ± 5.3 kg; height: 1.80 ± 0.08 m) completed simulated combat under three randomized crossover conditions using a Latin square randomization design: preferred music (PM), 15 Hz binaural beats with preferred music (15 Hz-BPM), and control. Measurements included striking indices (frequency, velocity), cardiovascular responses, rating of perceived exertion (RPE), feeling scale, and post-exercise blood lactate. The kickboxers could not be blinded due to the inherent auditory nature of the beta-frequency binaural beats.ResultsResults demonstrated significant main and interaction effects for striking performance and physiological markers (p < 0.001, η2p ≥ 0.29), indicating large effect sizes across primary outcomes. In addition, significant effects of round condition (p ≤ 0.027) for psychological parameters, while only a significant interaction effect was found for feeling scale and upper body RPE (p ≤ 0.005). Post-hoc analyses revealed that 15 Hz-BPM produced substantial improvements in striking frequency (η2p = 0.29–0.33) and peak velocity compared to music-only and control conditions, with effect sizes indicating practically meaningful performance enhancements. Similarly, our results showed a significant improvement for heart rate, feeling scale and a significant decrease for RPE and lactate values post-round in the 15 Hz-BPM than in the other conditions.ConclusionCombined preferred music and 15 Hz binaural beats during inter-round recovery enhanced striking performance and psychophysiological responses compared to single interventions or control conditions. These results suggest potential use of binaural beats and preferred music for performance optimization in amateur combat sports training.